The Impact 0f Playing Games and the Role Of Parents to Control Student Behaviour in Online Learning From a Teacher's Perspective Amid Pandemic Covid-19 - Bahagia, Bahagia; Wibowo, Rimun; Muniroh, Leny; Wahid, Azhar Al; Rizkal, Rizkal; Noor, Zakky Muhammad; Halim, Abdul Karim (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to find the positive and negative impacts of online learning on students' behavior in playing games. At the same time to find the best method for students not to spend time playing games and the role of parents to control student behavior. The research method used is descriptive qualitative and sampling method with purposive technique. While the sampling method used observation, interviews, and documentation. The results show that when learning online, students will participate in playing games, causing students to be lazy to study, undisciplined, enter online classes, and students' behavior becomes aggressive towards negative because they lose playing games. Games also have a positive impact as entertainment for students and learn strategies in problem-solving and educate the brain. Another finding is that online learning causes obesity and eye disease in students due to radiation exposure. Parents play an active role in controlling behavior by diverting children to find positive things such as children being told to look for language lessons online so that time is spent studying compared than playing games and social media. Parents should be friends with children and listen to children so that children are close to their parents.Keywords: Electronic device, game advantage, game detrimental, parent, covid-19